PENGARUH PENGETAHUAN, RESIKO, DAN SIKAP KEUANGAN, ETIKA BISNIS, KEPRIBADIAN TERHADAP PERILAKU MANAJEMEN KEUANGAN PADA PELAKU USAHA MIKRO DI LUBUK BAJA KOTA BATAM - Catur Fatchu Ukhriyawati; Fanny Islami Nasution; Rahmi Yuliana; Sriwati Sriwati (Jurnal Akuntansi dan Pajak, 2023)
This research aims to test and analyze the influence of knowledge, risk, and financial attitude, business ethics, personality on financial management behavior in micro-business actors in Lubuk Baja Batam City. This type of research is quantitative. The sampel of this study is Food and Bevarage Vendors in Lubuk Baja Batam City which numbered 80 people. Data analysis uses multiple regressions and hypothesis test using the help of IBM SPSS version 25. The result of this study can be concluded knowledge, risk, financial attitudes, business ethics, personality have a positive and significant effect on financial management behavior. Keyword: Knowledge, Risk, Financial Attitude, Business Ethics, Personality, Financial Management Behavior